Native high-density lipoprotein and melatonin improve platelet response induced by glycated lipoproteins - (:unkn) unknown (Charles University, 2018)
Activated platelets and glycated lipoproteins are responsible for atherothrombosis in diabetics. Melatonin and native high-density lipoproteins are crucial in the preservation of pro/oxidant-antioxidant balance. The aim of the present study was to investigate the in vitro effects of native high-density lipoproteins and melatonin on altering the platelet response induced by glycated lipoproteins. Low-density lipoproteins and high-density lipoproteins were purified from plasma by ultracentrifugation and were glycated with glucose for three weeks. After incubation with or without melatonin/or native high-density lipoproteins, low-density lipoproteins, glycated low-density lipoproteins/glycated high-density lipoproteins were added to ADP-induced platelets. Oxidative parameters, caspase-3/9 and nitric oxide levels were measured spectrophotometrically; CD62-P/ annexin-V expression was determined by flow cytometry. In glycated low-density lipoprotein/glycated high-density lipoprotein-treated groups, platelet malondialdehyde/protein carbonyl, P-selectin, annexin-V, caspase-3/9 levels were increased (ranging from P < 0.001 to P < 0.01); glutathione and nitric oxide levels were reduced (ranging from P < 0.001 to P < 0.01). In glycated low-density lipoprotein/glycated high-density lipoprotein-treated groups, melatonin treatment reduced malondialdehyde, protein carbonyl, CD62-P, annexin-V and caspase-3/9 (P < 0.001, P < 0.01) levels and elevated nitric oxide (only glycated low-density lipoproteins). In glycated low-density lipoprotein/glycated high-density lipoprotein-treated groups, native high-density lipoprotein treatment reduced malondialdehyde, protein carbonyl, annexin-V, caspase-3/9 levels (P < 0.001, P < 0.01) and increased glutathione; nitric oxide levels (only with gly-HDL). Both melatonin and high-density lipoproteins should be regarded as novel promising mechanism-based potential therapeutic targets to prevent atherothrombosis in diabetics. © 2018 Charles University. All rights reserved.
Keywords: High-density lipoproteins; In vitro glycation; Low-density lipoproteins; Melatonin; Platelets